Large-scale modeling - a tool for conquering the complexity of the brain - Djurfeldt, Mikael; Ekeberg, Örjan; Lansner, Anders (Frontiers in Neuroinformatics, 2008)
Is there any hope of achieving a thorough understanding of higher functions such as perception, memory, thought and emotion or is the stunning complexity of the brain a barrier which will limit such efforts for the foreseeable future? In this perspective we discuss methods to handle complexity, approaches to model building, and point to detailed large-scale models as a new contribution to the toolbox of the computational neuroscientist. We elucidate some aspects which distinguishes large-scale models and some of the technological challenges which they entail.